A 4‐mm Radius Curved Display with Touch Screen. Issue 1 (June 2014) - Ikeda, Takayuki; Nakamura, Daiki; Ikeda, Masataka; Iwaki, Yuji; Ikeda, Hisao; Watanabe, Kazunori; Miyake, Hiroyuki; Hirakata, Yoshiharu; Yamazaki, Shunpei; Kurosaki, Daisuke; Ohno, Masakatsu; Bower, Chris; et al.
Abstract We discuss the steps for obtaining a curved touch‐enabled display by using a c‐axis aligned crystalline oxide semiconductor, OLEDs, a flexible‐display technology, and a capacitive touch screen. This result is a side‐roll display in which the front and side surfaces are a single curved surface with a 4 mm radius.